Genome analysis of NDM-1 producing Morganella morganii clinical isolate. Issue 10 (October 2014) - Olaitan, Abiola Olumuyiwa; Diene, Seydina M; Gupta, Sushim Kumar; Adler, Amos; Assous, Marc Victor; Rolain, Jean-Marc
<x xml:space="preserve">Abstract</x> Objective: To analyze the resistome and virulence genes of Morganella morganii F675, a multidrug-resistant clinical isolate using whole genome sequencing (WGS). Methods: M. morganii F675 was isolated from a patient from Jerusalem, Israel. WGS was performed using both 454 and SOLiD sequencing technologies. Analyses of the bacterial resistome and other virulence genes were performed in addition to comparison with other available M. morganii genomes. Results: The assembled sequence had a genome size of 4, 127, 528 bp with G+C content of 51%. The resistome consisted of 13 antibiotic resistance genes including blaNDM-1 located in a plasmid likely acquired from Acinetobacter spp. Moreover, we characterized for the first time the whole lipid A biosynthesis pathway in this species along with the O-antigen gene cluster, the urease gene cluster and several other virulence genes. Conclusion: The WGS analysis of this pathogen further provides insight into its pathogenicity and resistance to antibiotics.